Cross-Border Exchanges: A Bibliometric Analysis Of Pak-Afghan Bilateral Trade Dynamics And Future Research Agenda - Sibghatullah Bangakh , Dr. Sheikh Usman Yousaf , Dr. Bushra Usman (Migration Letters, 2024)
Purpose: This study will conduct a bibliometric analysis to map the intellectual structure, key themes, influential publications, and research trends in the domain of Pak-afghan trade and transit. The objective will be to fill a niche on the topic in question. Methodology: Data was gathered from Google Scholar and Scopus databases. The analytical tools used is VOS Viewer, which includes co-citation mapping, bibliographic coupling, and co-word analysis. The pattern of citations, the co-authorship networks, and the keyword co-occurrence in the papers regarding Pak-Afghan trade and transit were subjected to analysis.[1] Findings: important topics, landmark publications, and major trends and gaps in the field. The inadequacy of ICT, political hostility, security issues, and various other factors, were also among the issues that are faced in bilateral trade. Opportunities for policy-level intervention and regional initiatives for improvement in trade relations were also pointed out. Contributions: This study is a rare examination of Pak-Afghan bilateral trade using bibliometric analysis. Such findings would elucidate the complexity of interactions in the realm, making this area a fertile one for further research on regional economic cooperation and trade dynamics. Policy Implications: This findings of the research point toward a dire need for strategies to remove impediments hindering Pak-Afghan trade relations. The policymakers should focus on the reduction of trade barriers, such as customs delays, infrastructural constraints, and nontariff barriers, through the enforcement of agreements like APTTA and ATTA. Improved political stability and governance along these trade routes, alternation of improved alternative trade routes, and people-to-people connections through easy visa procedures and cultural exchange can further improve trade relations. Addressing these issues will create a conducive environment for robust trade, contributing to regional stability and economic growth. Keywords: Pak-Afghan Trade, Bibliometric Analysis, Regional Economic Integration, Trade Barriers, Geopolitical Dynamics, VOS-Viewer.